2022
DOI: 10.1111/ene.15554
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms of COVID‐19 in patients with multiple sclerosis

Abstract: Background and purpose Clinical outcomes of multiple sclerosis (MS) patients affected by coronavirus disease 2019 (COVID‐19) have been thoroughly investigated, but a further analysis on main signs and symptoms and their risk factors still needs attention. The objective of this study was to group together and describe based on similarity the most common signs and symptoms of COVID‐19 in MS patients and identify all factors associated with their manifestation. Method Logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Furthermore, in another examination, it was demonstrated that among 39 MS patients with COVID-19, the distribution of psychiatric manifestations, such as depression and anxiety, is 10.25% (34). Correspondingly, several studies have reported neurologic symptoms in individuals diagnosed with both MS and COVID-19 (38)(39)(40).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in another examination, it was demonstrated that among 39 MS patients with COVID-19, the distribution of psychiatric manifestations, such as depression and anxiety, is 10.25% (34). Correspondingly, several studies have reported neurologic symptoms in individuals diagnosed with both MS and COVID-19 (38)(39)(40).…”
Section: Discussionmentioning
confidence: 96%
“…In an Italian report of 1354 patients with MS and confirmed SARS-CoV-2 infection, the symptoms were similar to those without MS, such as fever, fatigue, cough, dyspnea, anosmia, and ageusia. However, the treatment for MS with the B cell-depleting anti-CD20 therapies (rituximab, ocrelizumab, ofatumumab, and ublituximab) [ 141 ], was associated with an increase in SARS-CoV-2 general symptoms, neurological disorders (weakness, fatigue, asthenia, and cognitive symptoms), conjunctivitis, and rash [ 142 ]. Recent data shows that patients on rituximab have a fourfold increased risk of SARS-CoV-2 hospitalizations [ 140 , 143 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recent data shows that patients on rituximab have a fourfold increased risk of SARS-CoV-2 hospitalizations [ 140 , 143 ]. On the other hand, they reported a protective role with the use of teriflunomide, natalizumab, and fingolimod, reducing the shortness of breath, tachycardia, and chest pain, in patients with SARS-CoV-2 infection [ 142 ]. Some MS therapies, such as beta-interferons, fumarates, and sphingosine-1-phosphate (S1P), don’t seem to modify the course of COVID-19 infection.…”
Section: Reviewmentioning
confidence: 99%
“…AISM and FISM supported several data-sharing initiatives in the last years, promoting the development not only of the Italian MS Register, but also of databases to study different aspects of MS. This included initiatives such as the Italian Network of NeuroImaging (INNI) (47), the PROgnostic GEnetic Factors in Multiple Sclerosis (PROGEMUS) (48), the Multiple Sclerosis and COVID-19 (MuSC-19) platform (49), and Patient-Reported Outcome Measures for MS databases (PROMOPRO-MS) (50). Integration of PROMs with other outcomes will help to enable the holistic approach needed to unmask progression early in the disease.…”
Section: Italian Barcoding Ms Initiativementioning
confidence: 99%